2009
DOI: 10.1002/ange.200805894
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Single‐Nanoparticle Oxygen Sensors for Biological Imaging

Abstract: Sicheres Auge für Sauerstoff: Mit einem Platinporphyrin‐Farbstoff dotierte, konjugierte Polymernanopartikel weisen eine helle Phosphoreszenz auf, die sehr empfindlich auf die Konzentration von molekularem Sauerstoff reagiert. Ihre geringe Größe, ihre große Helligkeit und Empfindlichkeit, ihre ratiometrische Emission sowie ihre Zellgängigkeit könnten die Nanopartikel zu Sensoren in der quantitativen Erfassung lokaler Sauerstoffkonzentrationen machen.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 36 publications
2
54
0
6
Order By: Relevance
“…Wu and colleagues demonstrated that loading PtOEP into the conjugated polymer nanoparticle resulted in efficient energy transfer (∼89%) from the polymer to the porphyrin. 149 This efficient transfer was confirmed by fluorescence lifetime measurements, which resulted in a faster decay rate in the porphyrin-doped sample (τ D −1 = 56 ns −1 ) than the undoped sample (τ D −1 = 9 ns −1 ). Last, the capability of this nanoparticle to detect oxygen in macrophage cells was tested with incubation medium with O 2 -and N 2 -saturated solutions.…”
Section: Oxygen Sensing Through Phosphorescence Quenchingsupporting
confidence: 51%
“…Wu and colleagues demonstrated that loading PtOEP into the conjugated polymer nanoparticle resulted in efficient energy transfer (∼89%) from the polymer to the porphyrin. 149 This efficient transfer was confirmed by fluorescence lifetime measurements, which resulted in a faster decay rate in the porphyrin-doped sample (τ D −1 = 56 ns −1 ) than the undoped sample (τ D −1 = 9 ns −1 ). Last, the capability of this nanoparticle to detect oxygen in macrophage cells was tested with incubation medium with O 2 -and N 2 -saturated solutions.…”
Section: Oxygen Sensing Through Phosphorescence Quenchingsupporting
confidence: 51%
“…[38][39][40] Many such probes have been reported, however O 2 sensing applications are quite rare. 31,34,41 Their main challenges include water-solubility, cell penetration and bio-distribution in cells, operational and storage stability. We and others showed that nanoparticle O 2 probes often have poor in-depth staining of 3D cell models.…”
Section: Brightmentioning
confidence: 99%
“…For simplification, we named such kind of probes/sensors as liquid format probes/sensors. Many liquid oxygen probes/sensors by using organic compounds, macromolecules, and/or nanoparticles [21][22][23][24][25][26][27][28][29][30][31][32][33] were developed. Among these probes/sensors, although many are for intracellular oxygen measurements [22][23][24]30,31,[34][35][36][37]; some liquid sensors were demonstrated to be extracellular sensors and were used for cell respiration and mitochondrial activity measurements [21,28,29].…”
Section: Introductionmentioning
confidence: 99%